Rhombic Split Ring Resonator (R-SRR) Structure on Rectangular Patch Antenna Design - Hassan, Nornikman; Ahmad, B. H.; Abd. Aziz, M. Z. A.; Othman, A. R. (2013)
Abstract- This work focusing on the effect of the complementary rhombic split ring resonator (R-SRR) structure of gain, return loss and the radiation pattern the rectangular patch antenna design. The basic rectangular patch antenna design had been simulated in CST Microwave Studio simulation software. Then, the single unit of the R-SRR had been added into the patch antenna design. The targeting frequency of this antenna is 2.40 GHz for Wireless Local Area Network (WLAN) application. Compared with the conventional microstrip patch antenna with the same aperture size, the performance gain of the patch antennas is improved obviously and suitable for targeting frequency of 2.40 GHz. The parametric studies done this work work are the different variation pattern of R-SRR, different distance between two RSRR structure and different size of R-SRR.